Effect of Protein and Mineral Improvement on the Perfomance of Growers Sheep - AKOUEDEGNI, COOVI GUENOLE; ABOH, BOYA ANDRÉ; ADANDEDJAN, COCOU CLAUDE; MENSAH, GUY APOLLINAIRE; Tossa, Isidore Gbégo (My University, 2014)
The current trials were initiated to help the goat keepers improve the nutritional status of grower goats with other alternative supplements offered by available cotton and mucuna seeds and locally made mineral lick. The performances of the growers such as growth rate of 12 months, weight at one year and mortality rate at post-weaning stage of 3 to 12 months were measured. The results showed that treatment effect on dry matter intake by growers was significant. The growers fed the seeds consumed significantly more dry matter than those fed sole palm frond. Treatment effect on digestible dry matter intake was highly significant. The mean digestible dry matter intake by growers in the period of 8 to 12 months ranged between 25.8 g in the control and 39.1 g/kg0.75/day in the mucuna seed without salt lick group. Treatment effect was highly significant. The growers fed diets supplemented with the seeds showed higher growth rate than those in the control. The growers fed diets supplemented with the seeds showed higher weight at one year compared to the control. The mean weight at one year varied from 12.0 kg in the growers fed the seed to 14.6 kg in treatments with mineral lick. Use of these sources of protein could help the household in providing feed for their goats especially in the dry season and also in increasing the size of household flocks.
Keywords: Cotton; mucuna; digestibility; intake; West African Dwarf (WAD) goat.